Digital Exclusion of Older People in the Era of Digital Transformation: The Role of Generation Z as Mediators of Technology Access - Annisa Fauziyyah; Ima Rohimah; Fatma Azzahra; Mirna Nur Alia Abdullah (Universitas Negeri Yogyakarta, 2026)
Digital transformation has transformed various aspects of people’s lives, yet not all groups have been able to adapt effectively, particularly older adults who are vulnerable to digital exclusion. This study aims to examine the forms of the digital divide among older adults and the role of Generation Z as mediators in bridging access to digital services. The method employed is a descriptive qualitative approach through a literature review, analysing various relevant academic sources. The findings indicate that the digital divide among the elderly is multidimensional, encompassing limited access to technology, low digital literacy, limited technical skills, information gaps, psychological factors, and digital service designs that are not yet inclusive. Furthermore, social factors such as limited social networks also reinforce digital exclusion among older adults. In this context, Generation Z plays a crucial role as mediators who not only provide technical assistance but also act as technology interpreters, facilitators of informal learning, and providers of psychological support. Interactions between older adults and Generation Z reflect the role of social capital in enhancing digital inclusion through trust and interpersonal relationships. Therefore, intergenerational collaboration is a key strategy in creating an inclusive digital transformation and empowering older adults to adapt independently in the digital age.